Effect of self-cementing properties on the resilient behaviour of recycled concrete aggregates used in base and subbase - Wang, Chong; Chazallon, Cyrille; Hornych, Pierre; Mouhoubi, Saida; Jing, Peng (Road Materials and Pavement Design, 2024)
International audience Sometimes, an increase of strength and stiffness of unbound pavement base and subbase layers built with recycled concrete aggregates (RCA) can be observed, known as selfcementing properties of RCA. However, the influence of self-cementing properties on the resilient deformation behaviour has not been thoroughly studied. In this research, the selfcementing properties, microstructure and resilient deformation behaviour of two different RCA, NRCA and ORCA, showing significantly different self-cementing properties, after curing for different times (1, 180, 360 and 720 days), were studied by calorimeter tests, mercury intrusion porosimetry (MIP) tests and repeated load triaxial tests (RLTT). The results indicate that the strong self-cementing properties of NRCA improve their microstructure, decreasing the number of macro-pores between particles and the void ratio. As a result, the resilient modulus of NRCA increases continuously, while resilient deviatoric strain and volumetric strain decrease with curing time. After curing for 720 days, the mechanical performance of NRCA is comparable to that of lightly bound materials, which is much better than that of traditional unbound granular materials, showing the advantage of using RCA in unbound pavement layers. On the contrary, for ORCA, showing negligible self-cementing properties, the resilient deformations are most constant.